Analysis of posters, banners, brochures etc. / Azizul Halim Yahya and Ismail Sudin - Yahya, Azizul Halim; Sudin, Ismail (Faculty of Communication and Media Studies (FCMS), 1994)
Advertising, a growing specialisation in business administration has been utilised since the 19th century with the beginning of the print media in large towns in Peninsula Malaysia. At that time Advertising is used to channel various information about products, services and ideas. In the 1990s election campaign the government used the concept of advertising in the form of propaganda to deliver messages. The use of this form of advertising was usually done during the time of election. This method was found to be effective in the effort to change the opinions of voters.